2006
DOI: 10.1111/j.1469-7580.2006.00500.x
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of histological assessments of dental development and age at death

Abstract: Histological analyses of dental development have been conducted for several decades despite few studies assessing the accuracy of such methods. Using known-period incremental features, the crown formation time and age at death of five pig-tailed macaques ( Macaca nemestrina ) were estimated with standard histological techniques and compared with known ages. Estimates of age at death ranged from 8.6% underestimations to 15.0% overestimations, with an average 3.5% overestimate and a 7.2% average absolute differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
0
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 26 publications
2
56
0
7
Order By: Relevance
“…Smith et al (2004) reported crown extension rates for a single M 3 mesiobuccal cusp (protoconid) of Graecopithecus freybergi, which is similar to the values reported here for chimpanzees. In contrast, cusp-specific extension rates for macaques (Macaca nemestrina) are two to four times higher than hominoid values (Smith, 2004;Smith et al, 2006). It appears that, among extant and fossil great apes and humans, extension begins at a rather high rate in the crown, which progressively slows towards the cervix (Dean, 1998a;Smith et al, 2004), and then speeds up after the first or second millimeter of root formation.…”
Section: Variation In Incremental Developmentmentioning
confidence: 93%
See 2 more Smart Citations
“…Smith et al (2004) reported crown extension rates for a single M 3 mesiobuccal cusp (protoconid) of Graecopithecus freybergi, which is similar to the values reported here for chimpanzees. In contrast, cusp-specific extension rates for macaques (Macaca nemestrina) are two to four times higher than hominoid values (Smith, 2004;Smith et al, 2006). It appears that, among extant and fossil great apes and humans, extension begins at a rather high rate in the crown, which progressively slows towards the cervix (Dean, 1998a;Smith et al, 2004), and then speeds up after the first or second millimeter of root formation.…”
Section: Variation In Incremental Developmentmentioning
confidence: 93%
“…To register cusps (or teeth) forming at the same time, accentuated lines in the enamel or dentine are usually identified and matched between cusps (or teeth). Alternatively, cessation of formation at death in developing teeth also allows cusps to be registered with one another (e.g., Dirks, 1998;Reid et al, 1998a;Smith et al, 2006).…”
Section: Incremental Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the remarkable production of a line coincident with birth in permanent first molars (M1s) allows developmental time to be registered with an individual's actual age. When this neonatal line can be identified and subsequent development assessed from enamel and dentine increments, age at death may be estimated to within 5% of an individual's true age (21)(22)(23). This histological approach is a substantial improvement over the nearly ubiquitous application of recent human or ape developmental standards to age juvenile hominins.…”
mentioning
confidence: 99%
“…12,22,23). Resolution of the debate regarding whether Neanderthals and modern humans follow disparate ontogenetic trajectories has been slowed by a lack of data from histological sections of teeth (2).…”
mentioning
confidence: 99%